1971
DOI: 10.1007/bf01002350
|View full text |Cite
|
Sign up to set email alerts
|

The membrane of catecholamine storage vesicles of adrenal medulla catecholamine fluxes and ATPase activity

Abstract: 1. A method of preparing isolated membranes of the catecholamine storing vesicles of the adrenal medulla is described. The membrane protein amounts to 23% of the total vesicular protein and still contains 0.1% of the catecholamine. 2. At 31‡C in the presence of ATP the membrane preparation accumulates catecholamine; in the absence of ATP, however, catecholamine is released into the medium. At 0‡C the catecholamine content of the membrane preparation remains unchanged, whether ATP is present or not, although a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1974
1974
1988
1988

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The uptake process appears to be one of active transport, but the pH-dependence of the process suggests that it may not be linked directly to Mg++-ATPase activity (Taugner, 1971;Phillips, 1974). This work does not have a direct bearing upon the relationship between vesicle Mg++-ATPase and transmitter uptake and release in the central nervous system but it does suggest the processes may be related.…”
Section: Discussionmentioning
confidence: 77%
“…The uptake process appears to be one of active transport, but the pH-dependence of the process suggests that it may not be linked directly to Mg++-ATPase activity (Taugner, 1971;Phillips, 1974). This work does not have a direct bearing upon the relationship between vesicle Mg++-ATPase and transmitter uptake and release in the central nervous system but it does suggest the processes may be related.…”
Section: Discussionmentioning
confidence: 77%
“…The uptake of catecholamines is stoichiometrically related to a breakdown of A TP in the external medium (Kirshner et al, 1966), but there is no indication that A TP accompanies the catecholamine into the veside. Taugner (1971Taugner ( , 1972 has shown that amine uptake by medullary vesides is probably associated with a Mg 2 +-dependent ATPase in the veside membrane, which can be inhibited by sulfhydryl reagents (see below).…”
Section: Uptake Of Catecholamines and 5-ht By Storage Vesiclesmentioning
confidence: 97%
“…All procedures were carried out at 2-4°C. Purified catecholamine storage vesicles were obtained by density gradient centrifugation, essentially as described for the preparation of isolated membranes (Taugner, 1971). The vesicles which sedimented in 1.8 M-sucrose were lysed in 60 ml of 15 mM unbuffered KCI.…”
Section: Preparation Of the Water-soluble Proteinsmentioning
confidence: 99%